Cultural Acculturation of Ethnic Chinese and Ethnic Javanese in Kampung Ketandan Yogyakarta, 1966-2001 - Maghfirotull Fatkhiyah; Siska Nurazizah Lestari; Anggar Kaswati (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This study examines the cultural acculturation between Chinese and Javanese ethnic groups in Kampung Ketandan, Yogyakarta, during 1966-2001. The research aims to explore the factors driving and inhibiting this acculturation process. A historical method was employed, involving topic selection, heuristics, source verification, interpretation, and historiography. The findings reveal that the acculturation in Kampung Ketandan occurred harmoniously, marked by cultural adaptation processes such as deculturation, enculturation, acculturation, and assimilation manifesting in language, architecture, clothing, names, cuisine, and the arts. For example, the word